TRANSFORMATION OF PESANTREN CULTURE IN INTERNALIZING MULTICULTURALISM VALUES IN THE DIGITAL DISRUPTION ERA - Khoir, Qoidul (As-Sulthan Journal of Education, 2025)
This research examines the cultural transformation of pesantren in internalizing multiculturalism values in the digital disruption era. The research focus is directed toward changes in cultural, pedagogical patterns, and the role of pesantren leadership in responding to the dynamics of diversity and digital technological developments. This research uses a qualitative approach with a case study method thru in-depth interviews, participant observation, and document analysis. The research findings indicate that pesantren are undergoing a cultural shift from a hierarchical traditional pattern toward a more dialogical, inclusive, and adaptive culture thru the integration of moderate Islamic values, the utilization of digital media, and the strengthening of digital literacy and ethics. This transformation strengthens the role of pesantren as agents of religious moderation, but still faces obstacles such as the digital competency gap and limited contextual learning modules. The research conclusion confirms that the success of internalizing multiculturalism values in pesantren is highly determined by the visionary leadership of the kiai, the readiness of human resources, and institutional policy support. Therefore, this research recommends strengthening digital literacy, developing a multiculturalism-based pesantren curriculum, and implementing sustainable cultural transformation strategies to ensure that pesantren remain relevant and contribute to building an inclusive society in the digital age.